Juran on quality by design : - Juran, J. M. (Free Press, 1992)
Building on the experiences of scores of companies and hundreds of managers, J.M. Juran, the world-renowned quality pioneer, presents a new, exhaustively comprehensive approach to planning, setting, and reaching quality goals. Employing three case examples which encompass the three major sectors of the economy -- service, manufacturing, and support, he offers a practical plan for companies to achieve strategic, market-driven goals by following a structural approach to planning quality. Quality, according to Juran, has become a prerequisite for business success. He cites the loss of market share, failure of products, and waste as results of poor quality planning. Juran provides a set of universal steps which can be used in the basic managerial process to establish quality goals, identify customers, determine customer needs, provide measurement, and develop process features and controls to improve business tactics.